EFFECT OF MINDFULLNESS MEDITATION ON STRESS LEVEL AND COPING MECHANISM IN CANCER PATIENTS - Yesiana Dwi Wahyu Werdani (Folia Medica Indonesiana, 2017)
Cancer patients have a tendency to experience mental disorders, because the physical changes cause frustration and despair. It impacts on anxiety, depression, and social isolation. The purpose of this study was to analyze the influence of mindfullness meditation to stress levels and coping mechanisms in cancer patients. This study used pre experimental approach with one group pre-test post-test design. Samples were 32 cancer patients with composmentis condition in Indonesian Cancer Foundation East Java Branch, taken by total sampling. The instrument was Perceived Stress Scale and Coping Strategies Inventory. Statistics was verified with Wilcoxon Sign Rank Test and Paired T-test P < 0.05. Results showed the effect of Mindfulness Meditation on the level of stress p = 0.001, the adaptive of coping mechanisms p = 0.001 and maldaptive p = 0.003. In conclusion, Mindfulness meditation can cause the respondent to concentrate and focus on themselves, and also strengthen brain regions at the center of attention and executive function, interoception and mental flexibility.